Hate, crime and epistemic vulnerability: on sense-making and feelings of (un)safety among Danish Muslims - Flyvholm, Anne-Mai; Johansen, Birgitte Schepelern (Frontiers in Sociology, 2024)
This article investigates feelings of (un)safety emerging from knowing and sharing knowledge about hate crime and hate incidents. Drawing on fieldwork and interviews with young Muslims living in the greater Copenhagen area, the article explores the way the interlocutors seek to make sense of their experiences through available epistemic categories, and how this sense-making is shaped by reactions from the surrounding society, e.g., whether it is questioned, supported, ignored etc. Combining criminological and psychological research on direct and indirect harms of hate crime with insights from philosophy on epistemic encounters and their ethical implications the article provides a framework for investigating safety in epistemic interactions. Based on this framework, the article show the often hard work that people perform in order to balance epistemic needs (e.g. the need for knowledge and for recognition) with epistemic risks (e.g. the risk of testimonial rejection, of damaged epistemic confidence, or loss of credibility).